COMPARISON OF THE EFFECT OF FOREIGN DEBT ON ECONOMIC GROWTH OF INDONESIA IN THREE PERIODS OF GOVERNMENT - Endang Kusdiah Ningsih; Esty Naruliza; Asma Mario (EAJ (Economic and Accounting Journal), 2018)
This purpose of this articel is  to determine the ratio of the effect of foreign debt on economic growth. Since the reign of the Old Order  up to the reign of the Reform Order to date, the Indonesian government has always done debt (overseas loans). So as if the growth that accomplished by the Indonesian economy each year can not be separated from foreign debt.The data used are secondary data obtained from the Central Bureau of Statistics and Bank Indonesia. The analysis technique to be used is Quantitative Descriptive Method. The results of hypothesis test show that  the effect of foreign debt on economic growth only during the Reform Order.